TOLL LIKE RECEPTOR-4 GENE ASPARTATE 299 GLYCINE POLYMORPHISM IN SUDANESE PATIENTS WITH MYCETOMA - Musa, Mazin Babekir; Abdalsamad, Ismail; Mhmoud, Najwa. A.; Allzain, Haghamad; Bakhiet, Sahar M (International Journal of Research -GRANTHAALAYAH, 2021)
Background: Mycetoma is a neglected tropical disease characterized by deformity and disabilities with various medical, health, and socioeconomic impacts on the affected communities. The etiological factors associated with Mycetoma have not been fully understood, however genetic predisposition and inflammation are considered as Mycetoma risk factors. Toll like receptors (TLRs) are key players in the innate immune response and play a great role in immune-surveillance and inflammation. This study was conducted to investigate the potential role of TLR4 polymorphism (Asp299Gly) as a risk factor for development of Mycetoma. Objectives: To determine the presence of TLR4 polymorphism (Asp299Gly) in Sudanese Mycetoma patients as well as measuring allele frequency and genotype distribution of this mutation among Mycetoma patients and healthy controls. Material and Methods: The current study included ninety five (95) subjects, of whom fifty (50) were confirmed Mycetoma patients and forty five (45) were healthy volunteer controls. It was conducted at the Institute of Endemic Diseases and Mycetoma Research Centre; University of Khartoum in the period, from June 2015 to June 2016. DNA was isolated from blood samples of study subjects and TLR-4 gene polymorphism Asp299Gly was determined using PCR-RFLP with Nco1 restriction enzyme. Genotypes distribution and allele frequencies in the two groups were measured. Results and conclusion: There was insignificant difference in allele distribution of TLR4 (Asp299Gly) A/G (rs 4986790) in Mycetoma patients compared with the healthy controls. TLR4 (Asp299Gly) polymorphism (rs 4986790) was found in twenty(20) out of fifty (50) Sudanese patients with Mycetoma , that is forty percent (40%) and twenty seven (27) out of forty five (45) healthy control, that is sixty percent (60%). Further studies are needed in a large and ethnically diverse population to determine the impact of the TLR-4 polymorphism in the susceptibility to Mycetoma.